Factors impacting decision-making behavior of retail investors: envidence from Vietnam - Trần, Ngọc Quynh Nhu (2020)
This study investigates factors impacting investors’ decisionmaking behavior in Vietnam. Specifically, the research focuses on effects of information search include firm’s image search, accounting information search and subjective financial literacy